2008
DOI: 10.1002/ibd.20497
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of adenoma-like mass in chronic ulcerative colitis using a combined endoscopic mucosal resection and cap assisted submucosal dissection technique

Abstract: We have shown for the first time that endoscopic resection of ALM even in the presence of complicating mucosal fibrosis is technically achievable using a combined ESD-assisted EMR technique. In an appropriately selected cohort, this technique may provide a technically feasible and clinically acceptable therapy where otherwise colectomy would be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 21 publications
0
33
0
1
Order By: Relevance
“…Accordingly Smith et al [29] stated the efficacy and safety of the combined ESD-EMR using the Olympus KD-630 L insulation-tipped knife even for the resection of an adenoma-like mass in chronic ulcerative colitis in 67 patients. The authors reported at a median of 18 months follow-up, an overall cure rates for the ESD-assisted EMR cohort of 98% Bleeding complications occurred in 7/67 (10%) of cases in absence of bowel perforations.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly Smith et al [29] stated the efficacy and safety of the combined ESD-EMR using the Olympus KD-630 L insulation-tipped knife even for the resection of an adenoma-like mass in chronic ulcerative colitis in 67 patients. The authors reported at a median of 18 months follow-up, an overall cure rates for the ESD-assisted EMR cohort of 98% Bleeding complications occurred in 7/67 (10%) of cases in absence of bowel perforations.…”
Section: Discussionmentioning
confidence: 99%
“…However, mucosal and submucosal fibrosis induced by long-standing inflammatory activity in CUC makes it difficult to perform endoscopic resection of ALM. Recently, Smith et al reported the effectiveness of a combined endoscopic mucosal resection and cap-assisted submucosal dissection technique for adenoma-like mass in CUC [6]. Exactly, ESD-assisted EMR technique should be a promising treatment for ALM in CUC to avoid unnecessary surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported that as long as complete resection of circumscribed lateral spreading lesions and lesions with high grade dysplasia is achieved, these patients may be followed with surveillance. 109,110 In our practice, as long as patients have complete resection of polypoid or nonpolypoid lesions with no flat dysplasia elsewhere in the colon, we follow them with endoscopic surveillance with chromoendoscopy. Figure 6 highlights our approach to patients with endoscopically visible lesions in the setting of IBD.…”
Section: Endoscopic Polypectomymentioning
confidence: 99%